Discovery Learning pada Pembelajaran Klasifikasi Makhluk Hidup: Studi pada Siswa Kelas VII MTs Negeri 1 Bitung - Nuriyati Hadia; Helen J. Lawalata; Meity Tanor (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
The study used a pseudo-experimental design with a posttest-only control group design pattern. The population included the entire class VII, and the sample was randomly selected of two equivalent parallel classes, totaling 22 students each. The experimental class received the discovery learning treatment, while the control class used conventional methods. The research instrument is in the form of learning outcome tests in the form of objectives and essays that have been tested for validity and reliability. Data were analyzed through normality test, homogeneity test, and t-test of two independent samples at a significance level of 0.05. The results showed significant differences between the two groups. The average posttest score of the experimental class was 80.68 higher than the control class of 72.72. The analysis of the t-test yielded a t_hitung value of 2.74 greater than t_tabel 2.01, which means that the null hypothesis was rejected. The frequency distribution in the experimental class also showed a concentration of scores in the high category, while the control class was more dominant in the medium category. These findings confirm that discovery learning not only improves cognitive learning outcomes, but also encourages students' active engagement, motivation, and critical thinking skills. This study concludes that the implementation of discovery learning is effective in improving science learning outcomes in the classification of living things. Implicitly, teachers are advised to integrate this approach as an alternative to student-centered science learning strategies.